Strategies in Translating Wordplay in Perahu Kertas Novel from Indonesian to English - Rintan Ari Bonita (English Department, Faculty of Humanities, Andalas University, 2021)
The aims of this research are to identify wordplays found in the source-language text, classify them based on their types, and then analyze the strategies used to translate them. This research utilizes the descriptive qualitative approach. The data sources of this research were a novel entitled Perahu Kertas authored by Dewi Lestari as the source language text, and the translation of this novel entitled Paper Boat that was translated by Tiffany Tsao as the target language text. The theories apply in this research are the theories about Wordplay proposed by Dirk Delabastita (1993) and Leech (1969). After analyzing 20 data, the researcher found four types of Wordplay, they are phonological structure (homonymy, Homophony, and Paronymy), lexical development (Idiom), play on antonym, and punning repetition. Furthermore, four strategies used by translators in translating Wordplay are discovered as a result of this analysis. The four strategies used by the translator are Wordplay to Wordplay, Wordplay to non-wordplay, wordplay ST into wordplay TT, and Wordplay to zero. The main strategy used by the translator to convey the meaning of Wordplay is Wordplay to Wordplay.